2005
DOI: 10.1007/s10811-005-2999-z
|View full text |Cite
|
Sign up to set email alerts
|

Production of microcystins in calcareous Mediterranean streams: The Alharabe River, Segura River basin in south-east Spain

Abstract: The development of epilithic cyanobacteria communities in a Mediterranean calcareous stream in the province of Murcia (SE Spain) was studied during the course of one year in an attempt to clarify the environmental variables that influence the production of microcystins. The predominant cyanobacteria were species of Rivularia, which formed conspicuous colonies throughout the year. Seasonally, other species were abundant: Schizothrix fasciculata, Tolypothrix distorta and Phormidium splendidum. All the species co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 44 publications
6
29
0
1
Order By: Relevance
“…1d-f). Similar occurrence of both types of Rivularia on rocks in calcareous springs and streams has been described previously (Whitton, 2002), and are dominant in the majority of the Spanish rivers studied (Aboal et al, 2002(Aboal et al, , 2005. However, when the rivulariacean-type strains isolated from these calcareous rivers (Table 1), where Rivularia was dominant, were cultured under laboratory conditions and examined morphologically, all of them were very similar phenotypically (Fig.…”
Section: Resultssupporting
confidence: 82%
“…1d-f). Similar occurrence of both types of Rivularia on rocks in calcareous springs and streams has been described previously (Whitton, 2002), and are dominant in the majority of the Spanish rivers studied (Aboal et al, 2002(Aboal et al, , 2005. However, when the rivulariacean-type strains isolated from these calcareous rivers (Table 1), where Rivularia was dominant, were cultured under laboratory conditions and examined morphologically, all of them were very similar phenotypically (Fig.…”
Section: Resultssupporting
confidence: 82%
“…Most cyanotoxin research has been conducted on planktonic cyanobacteria because of the potential for bloom forming; however, recent studies show that benthic cyanobacteria can also produce toxins (Aboal et al, 2005;Mohamed et al, 2006;Izaguirre et al, 2007;Richardson et al, 2007). Of the five cyanobacterial genera isolated from the Cajati WSP, certain strains of Nostoc (Sivonen et al, 1990), Leptolyngbya (Richardson et al, 2007), and Phormidium (Aboal et al, 2005) have been reported as microcystin producers.…”
Section: Discussionmentioning
confidence: 99%
“…Of the five cyanobacterial genera isolated from the Cajati WSP, certain strains of Nostoc (Sivonen et al, 1990), Leptolyngbya (Richardson et al, 2007), and Phormidium (Aboal et al, 2005) have been reported as microcystin producers. Furthermore, two Leptolyngbya strains (NPLJ-34 and NPLJ-35), a Synechococcus elongatus strain (NPLB-1) and a Nostoc muscorum strain (NPBR-3) isolated from Brazilian water bodies, have been reported as hepatotoxic, although the specific toxin was not identified (Azevedo & Magalhães, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The lower parts of stalks sometimes have frequent epiphytic cyanobacteria, a taxonomic group which are well known to form microcystins (Codd et al, 2005). However, Aboal et al (2005) reported the presence of microcystins, especially microcystin LR, in the mucilaginous colonies of Cymbella affinis from the Alharabe R. in N-E Spain; the test samples did not include cyanobacteria, though cyanobacteria were frequent in the river and so the possibility of their microcystins being trapped in the Cymbella colonies could not be ruled out. Further studies (based on HPLC-mass spectrometry) have now indicated the presence of microcystins in two populations of D. geminata collected quite late in the growth season: Stony Gill (UK) in July 2000 and R. Puntledge (Vancouver Is) in September 2007 (M. Aboal, pers.…”
Section: Biotic Interactionsmentioning
confidence: 99%